1984
DOI: 10.1111/j.1365-2133.1984.tb07318.x
|View full text |Cite
|
Sign up to set email alerts
|

Syringolymphoid hyperplasia with alopecia

Abstract: A 26-year-old man presented with an unusual skin lesion consisting of a hairless area on the left leg studded with reddish-brown papules, together with follicular hyperkeratosis and circumscribed anhidrosis. Skin biopsies showed dense lymphocytic infiltrates in the dermis and around hyperplastic sweat ducts and glands. Similar clinical and histological features have been described in two previous case reports. We propose the term syringolymphoid hyperplasia with alopecia for this unusual skin disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1
3

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 11 publications
2
22
1
3
Order By: Relevance
“…So far, only few reports on cases of syringolymphoid hyperplasia with alopecia have been published [1][2][3][7][8][9][10][11][12][13]. Clinical, histological, immunohistochemical, and genotypic features of the case presented here are well compatible with the diagnosis of syringolymphoid hyperplasia as it has been previously defined in the literature.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…So far, only few reports on cases of syringolymphoid hyperplasia with alopecia have been published [1][2][3][7][8][9][10][11][12][13]. Clinical, histological, immunohistochemical, and genotypic features of the case presented here are well compatible with the diagnosis of syringolymphoid hyperplasia as it has been previously defined in the literature.…”
Section: Discussionsupporting
confidence: 73%
“…However, our patient did not benefit from either treatment. A review of the reported cases of syringolymphoid hyperplasia with alopecia showed that moisturizer, various topical and systemic glucocorticosteroids, hydroxychloroquine (200 mg/d), etretinate (25 mg/d) plus PUVA (8-methoxypsoralen, 0.6 mg/kg, + UVA), and surgery have been used as therapeutic treatments (table 1) [2,3,[7][8][9]12]. Zelger et al [3] reported that intermittent topical glucocorticosteroid therapy resulted in a moderate improvement of skin lesions.…”
Section: Introductionmentioning
confidence: 99%
“…5 It is now thought that virtually all cases of SLHA are syringotropic forms of MF. 3 However, the relationship between folliculotropic MF and syringotropic MF has remained unclear, especially regarding whether they overlap or precede one another and the difference in their prognosis.…”
mentioning
confidence: 99%
“…Alopecia, hypoesthesia, and anhydrosis are variably associated with this condition. 1,2 Occasionally, SCTCL presents with erythroderma, skin nodules or lymphadenopathy mimicking scleroderma, or Sézary syndrome. 3,4 It is reported that SCTCL could occur at sites of actinic exposure, theorizing that the relative depletion of Langerhan cells caused by sun damage could curtail immune surveillance and lead to this condition.…”
Section: Discussionmentioning
confidence: 98%